Privatization : expectations, trade-offs and results. - SCHWARTZ, Gerd (1993)
Notes that while privatization has increased rapidly around the world, the results in many countries have fallen short of initial expectations. In practice, privatization objectives are often in conflict, requiring trade-offs and compromises.